Efforts to Improve Islamic Education Students' Learning Outcomes at Alue Kuyun Elementary School Using Sharing Strategies and Audio Visual Media - Nur, Laila; Aisyah, Siti (Jurnal Profesi Guru Indonesia, 2025)
This research aims to increase the activeness and learning outcomes of students in learning Islamic Religious Education (PAI) material on Faith to the Prophet and Apostle in grade VI of SD Negeri Alue Kuyun through the application of sharing strategies combined with audio-visual media. This classroom action research was carried out in two cycles with each cycle consisting of two meetings. Student activity data was collected through observation, while learning outcomes were measured using written tests. The results of the study showed a significant improvement in both aspects. Student activity increased from 37.5% in the initial condition to 62.5% in the first cycle and reached 87.5% in the second cycle. Student learning outcomes also increased, with the percentage of students who reached the Minimum Completeness Criteria (KKM) of 56.25% in the initial condition, increased to 68.75% in the first cycle, and reached 81.25% in the second cycle. The average grade point also increased from 65.5 to 77.8. This study concludes that the application of sharing strategies combined with audio-visual media is effective in increasing student activity and learning outcomes in PAI learning at SD Negeri Alue Kuyun. The implications of this research can be used as a reference in the development of more interesting and interactive learning methods.